A USABILITY STUDY OF THE AUDIO-TACTILE MAP FOR VISUALLY IMPAIRED USERS AT THE MALAYSIAN ASSOCIATION FOR THE BLIND (MAB) - Agustine Anak Mawun; Norisan Abd Karim; Fariza Hanis Abdul Razak (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
At the Malaysian Association for the Blind (MAB) building, the audio-tactile map has been installed on the ground floor to help and guide visual impairments in wayfinding. However, the usability of the audio-tactile map in helping them in wayfinding at the MAB has not been tested yet. In fact, the understanding of the users’ motivation for using the audio-tactile map has still not been studied. Thus, this research aims to describe the usability and to understand users’ motivation in using the audio-tactile map for visually impaired users in wayfinding at the MAB. Furthermore, a qualitative method study will be conducted by doing a user test and an interview with six participants from the MAB, focusing on the usability and users’ motivation in using the audio-tactile map to help them in wayfinding. Nielson Usability Model and Thematic Analysis with Affinity Diagram tools were applied in this research to analyze the data. The findings from this research have described the usability of the audio-tactile map among visually impaired users at the MAB, which includes efficiency, learnability, satisfaction, errors, and memorability. Also, the findings showed that the audio-tactile map features affected the users’ motivation to use the audio-tactile map for wayfinding at the MAB.